STUDI DESKRIPTIF TINGKAT STRES KERJA PERAWAT GAWAT DARURAT DI RUANG INSTALASI GAWAT DARURAT RUMAH SAKIT Dr. BRATANATA JAMBI TAHUN 2010 - Rusmimpong Rusmimpong (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
The stress is on the body and mind disorder caused by the changes and demands of life, from the initial survey with interviews to nurse IGD found that some nurses complain with the demands of his job as nurse IGD, and the presence of impaired physical or emotional changesThe design of this research is Quantitative Descriptive using IE get a picture of the level of work stress of nurses in emergency room Emergency Installations which include signs and symptoms of physical, emotional, and psychological.The purpose of this research is to know the level of nurse's work stress measuring results with normal, light, medium, heavy, and very heavy. While the sample is taken using the technique of total sampling of nursing 30 installation of Emergency Hospital Dr. Slamet Bratanata Jambi.Data retrieval is performed using a questionnaire and then analyzed. To measure the results of this research is taken from the sum of the total score of all answers with0-22 (normal), 23-45 (mild), 46-68 (medium), 69-91 (weight), > 92 (very heavy). While the techniques analysis using univariate analysis.The results of this study showed a nurse with normal stress level was as much as 8 people (26.60%), mild stress as many as 19 people (63,30%), stress are 3 people (10.10%), while for the stress level is very heavy in weight and not be found.Thus to nurse stresnya level in the normal range, it can continue to improve mentalhealth by maintaining a balance in order for the resulting performance more maximum, whereas for the level of nurse stresnya the verge of normal limit is expected toknow the stress management by knowing the signs of stress and start making lifestyle changes with attention to diet and nutrition, exercising more and exercise, so thebody both physical endurance mental, can awake, keep the balance life between work, leisure, health, family, and worship. While nurses are not capable in stress management, can visit the experts/professionals who can help realize a normal response to stress.keyword : stress, management, respons